2010
DOI: 10.1038/hr.2010.189
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor induction in a pressure-overloaded heart ameliorated by the angiotensin II type 1 receptor blocker olmesartan

Abstract: Connective tissue growth factor (CTGF) is a secreted protein that regulates fibrosis. We hypothesized that CTGF is induced in a pressure-overloaded (PO) heart and that blocking the angiotensin II type 1 receptor would reduce CTGF expression. Accordingly, we administered olmesartan and compared its effects with other antihypertensive drugs in a PO heart. CTGF induction was determined in a rat PO model, and olmesartan, hydralazine or saline was continuously administered. The effects of olmesartan on CTGF inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…3). In the CCN family, CCN2 (connective tissue growth factor, CTGF) is supposed to promote hypertrophic reactions and fibrosis in pressure-overloaded heart, although its effect is indirect [12]. In contrast, it is suggested that CCN5 inhibits cardiac hypertrophy and fibrosis through effects on CCN2 [33].…”
Section: Discussionmentioning
confidence: 99%
“…3). In the CCN family, CCN2 (connective tissue growth factor, CTGF) is supposed to promote hypertrophic reactions and fibrosis in pressure-overloaded heart, although its effect is indirect [12]. In contrast, it is suggested that CCN5 inhibits cardiac hypertrophy and fibrosis through effects on CCN2 [33].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of angiotensin II to fibroblast culture elevated CCN2 mRNA and protein [19]. Pressure overload of the left ventricle of the heart caused increased expression of CCN2 protein, that was abolished by olmesartan -another AT1 receptor antagonist [20]. Although this protein may be responsible for increased deposition of connective tissue also in the atrial myocardium, there has been no direct investigation targeting this specific issue to date.…”
Section: Discussionmentioning
confidence: 99%
“…Marked and consistent CCN2 induction is found in cardiac hypertrophy due to pressure overload, or angiotensin II infusion (205), (134), in models of diabetic cardiomyopathy (476), in a porcine model of pacing-induced cardiomyopathy (10), in aging-associated murine cardiac fibrosis (473), in the mdx mouse model of dystrophic cardiomyopathy (22) and in a model of cardiac fibrosis due to viral myocarditis (247). Much like in the infarcted heart, TGF-β, angiotensin II and endothelin-1 may be involved in mediating CCN2 upregulation in the hypertrophied ventricle.…”
Section: The Matricellular Proteins Key Modulators Of Cell:cellmentioning
confidence: 98%